PKL-P Kemuhammadiyahan: Penguatan Literasi Keagamaan dan Pemberdayaan Umat di PRM Jayengan: PKL-P Kemuhammadiyahan: Strengthening Religious Literacy and Empowering People in PRM Jayengan - Ahmad Nurrohim; Andri Eka Saputra; Dafa Aditya Husodo; Ijai Varol Abiansyah; Irsyad Al Ghifari; Aditya Riza Pramudya (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This article explores the implementation of the Field Work Practice and Community Service Program (PKL-P) conducted at the Muhammadiyah Sub-Branch Leadership (PRM) in Jayengan. The initiative was structured around two primary objectives: first, to equip university students with meaningful hands-on experience in applying Muhammadiyah’s core values within the social fabric of the community; and second, to foster their proactive engagement in developing and empowering the PRM Jayengan society through community-based and locally responsive programs. Using a qualitative approach, the implementation involved participatory observation, in-depth interviews with PRM officials and local community figures, as well as detailed documentation of activities as data sources. The primary focus was directed at revitalizing religious learning activities and enhancing the quality of Qur’anic education provided at the local TPA (Qur’anic Learning Center). The findings indicate that student participants were not only successful in recognizing key challenges and opportunities within the community, but also in launching impactful service initiatives. These included greater congregation involvement in regular Islamic study sessions and the improved organization of TPA educational activities. Furthermore, the program played a significant role in cultivating a shared awareness of PRM’s importance as a community-guiding institution. In conclusion, the Muhammadiyah PKL-P program at PRM Jayengan offered transformative learning for students while simultaneously reinforcing the mission of Islamic propagation and community empowerment within the Muhammadiyah network.